Redesign of Coffee Enema Basket Using DFMA for Improved Efficiency - Amirullah , Adam Rizki; BAMBAN JAKARIA, RIBANGUN BAMBAN JAKARIA (Indonesian Journal of Cultural and Community Development, 2024)
The general background highlights the growing popularity of coffee enemas, necessitating improvements in product design for better usability and economic viability. The specific background addresses inefficiencies in existing enema basket designs, which often lack user-friendly features. The knowledge gap identified is the absence of systematic approaches to optimize both manufacturing and assembly processes for this product category. The aim of the research is to develop a more efficient and safer design by employing the DFMA methodology. Results indicate that the new design not only reduces the number of components by two but also achieves a 36% improvement in assembly time and a 13% reduction in assembly costs. The novelty of this study lies in the integration of additional safety features while maintaining component efficiency, enabling multiple uses through a removable filter design. The implications suggest that adopting DFMA in product development can significantly enhance both economic and functional aspects, providing a model for future designs in consumer health products. Further research is recommended to incorporate Quality Function Deployment (QFD) for gathering consumer feedback to refine the design according to user preferences. Highlights: The study uses DFMA to enhance the efficiency and safety of coffee enema baskets. The new design reduces assembly time by 36% and costs by 13%. Incorporation of safety features and a removable filter for multiple uses addresses existing usability issues. Keywords: Coffee Enema, DFMA, Product Design, User Safety, Assembly Efficiency